Examining iron complexes with organic ligands by laboratory XAFS. Issue 2 (18th January 2023) - Motz, Damian; Praetz, Sebastian; Schlesiger, Christopher; Henniges, Jonathan; Böttcher, Florian; Hesse, Bernhard; Castillo-Michel, Hiram; Mijatz, Steven; Malzer, Wolfgang; Kanngießer, Birgit; Vogt, Carla
Abstract : This paper presents the application of laboratory X-ray Absorption Fine Structure Spectroscopy (XAFS) in the field of iron coordination chemistry, especially for compounds with larger organic ligands and usually low contents of the metal. Abstract : This paper presents the application of laboratory X-ray Absorption Fine Structure Spectroscopy (XAFS) in the field of iron coordination chemistry, especially for compounds with larger organic ligands and usually low contents of the metal. The goal was to compare the efficiency of the laboratory setup with the synchrotron setups usually applied for the determination of the oxidation and coordination states of heavier elements and to investigate the limits of the tabletop system for the discrimination of complexes with similar ligands. For the measurement of iron K-edge XANES spectra at the laboratory, an X-ray tube-based spectrometer using the von Hamos geometry with a Highly Annealed Pyrolytic Graphite (HAPG) mosaic crystal optic was used, and synchrotron measurements were performed at the beamline ID21 at the ESRF. Different iron complexes, such as iron(ii )-2, 6-Bis(benzimidazol-2-yl)pyridine systems, iron(iii )-porphyrins and human hemoglobin, have been successfully measured with both setups. With an energy resolving power of about E /Δ E = 4000 around the iron K-edge for the laboratory setup, the results can compete with synchrotron measurements with a Si(111) crystal monochromator and a resolving power of about E /Δ E = 5070. The findings of this work show that laboratory XAFS is also beneficial for applications in coordination chemistry such as the investigation of metal complexes with organic ligands. Thus, the results complement the ongoing continuous developments and improvements of various laboratory XAFS setups with high resolution, moderate measuring times and standardized sample preparation techniques as well as increasing applications in multiple fields of analytical chemistry. These improvements and continuously growing applications will further increase the spread and acceptance of laboratory XAFS.